2022
DOI: 10.1111/jfb.15021
|View full text |Cite
|
Sign up to set email alerts
|

Starter feed for carnivorous species as a practical replacement of bloodworms for a vertebrate model organism in ageing, the turquoise killifish Nothobranchius furzeri

Abstract: The absence of a controlled diet is unfortunate in a promising model organism for ageing, the turquoise killifish (Nothobranchius furzeri Jubb, 1971). Currently captive N. furzeri are fed bloodworms but it is not known whether this is an optimal diet. Replacing bloodworms with a practical dry feed would reduce diet variability. In the present study, we estimated the nutritional value of the diet ingested by wild fish and determined the fish‐body amino acid profile as a proxy for their nutritional requirements.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 84 publications
0
9
0
Order By: Relevance
“…The starter feed plays a crucial role in supplying trace elements and essential nutrients necessary for the growth and development of juvenile animals, especially during the early weaning stage [2,14,15]. Research indicates that the early introduction of starter feed can promote rumen development and facilitate early weaning [16].…”
Section: Discussionmentioning
confidence: 99%
“…The starter feed plays a crucial role in supplying trace elements and essential nutrients necessary for the growth and development of juvenile animals, especially during the early weaning stage [2,14,15]. Research indicates that the early introduction of starter feed can promote rumen development and facilitate early weaning [16].…”
Section: Discussionmentioning
confidence: 99%
“…Females had stronger predation pressure on prey than males regardless of water turbidity. Females in natural populations commonly exhibit a higher feeding rate, where females have fuller guts (Žák et al., 2022). Females have undoubtedly higher nutritional demands than males in regard to reproduction because they have larger gonads (Vrtílek & Reichard, 2016), they oviposit dozens of eggs daily (Žák et al., 2019) and have higher metabolism than males (Methling et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The order of treatments had no effect on experimental outcomes and was omitted from all relevant models. Fish were fasted overnight which is satisfactory to empty their digestive tracts (Žák et al., 2022). Each fish was weighed for wet body mass with precision of 0.1 g (Lesak P221, Czech Republic) prior to release into the experiment.…”
Section: Methodsmentioning
confidence: 99%
“…In such a situation, to fast-track SRD development, background work accelerating the process is needed. For example, a previous study on aging in a model vertebrate organism, the turquoise killifish Nothobranchius furzeri , showed that both its growth and reproductive potential are highly manipulable depending on the diet used in the laboratory 4 . In our previous study 5 , we explored how macronutrients in feed, energy, and amino acids affect somatic growth in marbled crayfish.…”
Section: Introductionmentioning
confidence: 99%
“…As such, ornamental fish feeds are not intended to ensure optimum growth and physiology or be species-specific 19 . These traditionally used ornamental fish feeds are often deficient in certain nutrients, so growth can be slower 4 , 5 , causing micronutrient deficiencies 20 and generational turnover may take longer. Although efforts have been made to understand preferences for amino acids in marbled crayfish 16 (see our previous study 5 ), research is yet to explore the preferences for fatty acids that affect the speed at which maturation and accompanied glair gland formation appear 21 .…”
Section: Introductionmentioning
confidence: 99%